Respuesta :
[tex]\\ \sf\longmapsto f(x)=2x^2-3x+1[/tex]
[tex]\\ \sf\longmapsto f(1)=2(1)^2-3(1)+1[/tex]
[tex]\\ \sf\longmapsto f(1)=2(1)-3+1[/tex]
[tex]\\ \sf\longmapsto f(1)=0[/tex]
Now
[tex]\\ \sf\longmapsto f(2)=2(2)^2-3(2)+1[/tex]
[tex]\\ \sf\longmapsto f(2)=2(4)-6+1[/tex]
[tex]\\ \sf\longmapsto f(2)=8-5[/tex]
[tex]\\ \sf\longmapsto f(2)=3[/tex]
Answer:
[tex]\sf{f(x)=2x^{2}-3x+1}[/tex]
We have to evaluate this following equation .
[tex]f(x)=2x^2-3x+1\\\\f(1)=2(1)^2-3(1)+1\\\\f(1)=2-3+1\\\\f(1)=3-3\\\\f(1)=0[/tex]
[tex]\\\\\\[/tex]
[tex]f(x)=2x^2-3x+1\\\\f(2)=2(2)^2-3(2)+1\\\\f(2)=8-6+1\\\\f(1)=9-6\\\\f(1)=3[/tex]